2016
DOI: 10.20944/preprints201610.0044.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using MODIS Data to Predict Regional Corn Yields

Abstract: A simple approach was developed to predict corn yields using the MoDerate Resolution Imaging Spectroradiometer (MODIS) data product from two geographically separate major corn crop production regions: Illinois, USA and Heilongjiang, China. The MOD09A1 data product, which are 8-day interval surface reflectance data, were obtained from day of the year (DOY) 89 to 337 to calculate the leaf area index (LAI). The sum of the LAI from early in the season to a given date in the season [end of DOY (EOD)] was well fitte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Experiments have shown that phenological dynamic information can solve this heterogeneity issue and improve the yield prediction or estimation accuracy [ 25 , 26 ]. For example, the accumulative leaf area index (LAI) in a specific GP had the highest correlation with the regional crop yield [ 27 ], and the time series index, combined with phenological date information, can effectively improve the yield prediction accuracy [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that phenological dynamic information can solve this heterogeneity issue and improve the yield prediction or estimation accuracy [ 25 , 26 ]. For example, the accumulative leaf area index (LAI) in a specific GP had the highest correlation with the regional crop yield [ 27 ], and the time series index, combined with phenological date information, can effectively improve the yield prediction accuracy [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%